2013
DOI: 10.1002/ps.3683
|View full text |Cite
|
Sign up to set email alerts
|

A mutation (L1014F) in the voltage‐gated sodium channel of the grain aphid, Sitobion avenae, is associated with resistance to pyrethroid insecticides

Abstract: The L1014F (kdr) mutation, known to confer pyrethroid resistance in many insect pests, has been identified for the first time in S. avenae. Clonal lines heterozygous for the mutation showed 35-40-fold resistance to lambda-cyhalothrin in laboratory bioassays, consistent with the reported effect of this mutation on pyrethroid sensitivity in other aphid species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
92
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 17 publications
3
92
0
Order By: Relevance
“…For example, owing to aphid damage average yields have been estimated to fall by 700 000 tonnes annually across Europe and it has also been shown that aphids can cost the American economy up to $274 million (Dedryver et al, 2010). Recently, chemical intervention by farmers has triggered aphid resistance mechanisms to pyrethroids that are commonly used to protect crops against aphid feeding damage (Foster et al, 2014). The constant evolution and resistance to chemical control and the EU-enforced reduction of insecticides available to farmers both serve to highlight the value of conservation biological control as a tool to help regulate aphid populations (Schmidt et al, 2003;Meiners & Peri, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, owing to aphid damage average yields have been estimated to fall by 700 000 tonnes annually across Europe and it has also been shown that aphids can cost the American economy up to $274 million (Dedryver et al, 2010). Recently, chemical intervention by farmers has triggered aphid resistance mechanisms to pyrethroids that are commonly used to protect crops against aphid feeding damage (Foster et al, 2014). The constant evolution and resistance to chemical control and the EU-enforced reduction of insecticides available to farmers both serve to highlight the value of conservation biological control as a tool to help regulate aphid populations (Schmidt et al, 2003;Meiners & Peri, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Resistance can spread extremely fast after its initial emergence. For example, the frequency of mutations associated with pyrethroid resistance has increased 50-to 1,000-fold in insects such as aphids and mosquitoes in less than a decade (7,8).…”
mentioning
confidence: 99%
“…Renewed interest in understanding aphid behaviour and host preferences are largely due to the recent development of insecticide resistance in many aphid species13 which, coupled with increasing restrictions on insecticide use14, are causing serious concerns for food security. Wheat is a crop of high economic importance as it is a main ingredient of many diets around the world1516.…”
mentioning
confidence: 99%
“…Currently the main measure used to control pest populations are insecticides, however; S. avenae populations have developed resistance to classes of pesticides rendering them ineffective13, resulting in widespread infestation18 and focusing efforts on finding alternative control methods.…”
mentioning
confidence: 99%